Zebrafish do not have a calprotectin ortholog. - Kona N Orlandi; Michael J Harms (PLoS ONE)
The protein heterodimer calprotectin and its component proteins, S100A8 and S100A9, play important antibacterial and pro-inflammatory roles in the mammalian innate immune response. Gaining mechanistic insights into the regulation and biological function of calprotectin will help facilitate patient diagnostics and therapy for inflammation and further our understanding of the host-microbe interface. Recent literature has identified zebrafish s100a10b as zebrafish calprotectin based on sequence similarity, genomic context, and transcriptional upregulation during the immune response to bacterial infections. The field would benefit from expanding the breadth of calprotectin studies into a zebrafish innate immunity model. Here, we carefully evaluated the possibility that zebrafish possess a calprotectin ortholog or a paralog that convergently evolved similar function. Using careful bioinformatics approaches, we found that zebrafish do not have an ortholog of either mammalian S100A8 or S100A9. To look for paralogs with convergent function, we identified four zebrafish s100 proteins-including s100a10b-that are expressed in immune cells and upregulated during the immune response. We recombinantly expressed and purified these proteins and measured their antimicrobial activity. None of the zebrafish proteins exhibited activity comparable to mammalian calprotectin. We also generated structural models of all homodimers and heterodimers of all annotated zebrafish s100 genes. None of these complexes were predicted to have an antimicrobial transition metal binding site equivalent to calprotectin. Finally, we measured the ability of our four purified zebrafish s100 proteins to activate inflammation via Toll-like receptor 4, a key feature of human S100A9; none of the proteins activated the receptor. Our work demonstrates conclusively that zebrafish have no ortholog of calprotectin and suggests that similar proteins have not convergently evolved analogous functions.